Elements of the Quantum Novel: Creció espesa la yerba, by Carmen Conde - Orozco Abarca, Giovanni (2026)
This research analyzes how the novel Creció espesa la yerba (1979), by Carmen Conde, fits within quantum literature, having characteristics such as the presence of multiple spatiotemporal dimensions, time indeterminacy (suspension and past-present-future fusion), and the use of the wormhole as a literary device. The characters are fragments of a larger structure, and the narrative incorporates the principle of indeterminacy through chance, dreams, and the awful. Therefore, the novel departs from traditional narrative techniques by employing quantum strategies such as character bilocation and fractality to construe its plot.